The influence of service quality, trust and reputation on customer satisfaction : evidence from public hospitals in Jordan - Hamza Ali Mohammad Alshatnawi (School of Business Innovation and Technopreneurship, Universiti Malaysia Perlis, 2014)
This masters' thesis sought to assess and analyse customer satisfaction with service quality (Tangible, Reliability, Responsiveness, Assurance and Empathy), Trust and Reputation in the public hospitals in Jordan. Specifically, it examined the determinants of satisfaction and the effects of customer satisfaction on waiting time and medical care in Jordan's public hospitals.